CD8+ T Cells Form the Predominant Subset of NKG2A+ Cells in Human Lung Cancer - Chen, Yongyuan; Xin, Zhongwei; Huang, Lijian; Zhao, Lufeng; Wang, Shijie; Cheng, Jiwei; Wu, Pin; Chai, Ying (Frontiers in Immunology, 2020)
Background: NKG2A is an inhibitory receptor of both T cells and natural killer (NK) cells. Persistent activation promotes T cells and NK cells to express NKG2A and results in the progression of chronic infection and cancer. However, the characteristics and subsets of NKG2A+ lymphocytes in human lung cancer are still unclear. Methods: Here, we used the Tumor Immune Estimation Resource (TIMER) database and immune profiling of paired biospecimens to uncover the correlation between NKG2A expression and immune infiltration levels in human cancer as well as the characteristics of NKG2A+ lymphocytes in human lung cancer. Results: We found that KLRC1 expression was especially correlated with CD8+ T cell infiltration levels in 34 types of human cancer through the TIMER database. Moreover, NKG2A+ CD8+ T cells were the predominant subset of NKG2A+ lymphocytes in human lung cancer. In contrast, the NKG2A+ NK cells were decreased in tumors compared with the paired normal lung tissue. Tumor-infiltrating NKG2A+ CD8+ T cells expressed tissue-resident memory T cell (TRM cell) and exhausted T cell markers. Cytokines and cytotoxic molecules secreted by tumor-infiltrating NKG2A+ CD8+ T cells were significantly lower than those secreted by NKG2A- CD8+ T cells in vitro. When stimulated with T cell receptor (TCR) activator, tumor-infiltrating NKG2A+ CD8+ T cells could secrete large amounts of granzyme B. Conclusions: Our findings demonstrate that tumor-infiltrating NKG2A+ CD8+ T cells form the predominant subset of NKG2A+ cells in human lung cancer and suggest that targeting NKG2A+ CD8+ T cells is a promising approach for future anti-lung cancer immunotherapy.